'Clinically unnecessary' use of emergency and urgent care: A realist review of patients' decision making. (29th October 2019) - O'Cathain, Alicia; Connell, Janice; Long, Jaqui; Coster, Joanne
Abstract: Background: Demand is labelled 'clinically unnecessary' when patients do not need the levels of clinical care or urgency provided by the service they contact. Objective: To identify programme theories which seek to explain why patients make use of emergency and urgent care that is subsequently judged as clinically unnecessary. Design: Realist review. Methods: Papers from four recent systematic reviews of demand for emergency and urgent care, and an updated search to January 2017. Programme theories developed using Context‐Mechanism‐Outcome chains identified from 32 qualitative studies and tested by exploring their relationship with existing health behaviour theories and 29 quantitative studies. Results: Six mechanisms, based on ten interrelated programme theories, explained why patients made clinically unnecessary use of emergency and urgent care: (a) need for risk minimization, for example heightened anxiety due to previous experiences of traumatic events; (b) need for speed, for example caused by need to function normally to attend to responsibilities; (c) need for low treatment‐seeking burden, caused by inability to cope due to complex or stressful lives; (d) compliance, because family or health services had advised such action; (e) consumer satisfaction, because emergency departments were perceived to offer the desired tests and expertise when contrasted with primary care; and (f) frustration, where patients had attempted and failed to obtain a general practitioner appointment in the desired timeframe. Multiple mechanisms could operate for an individual. Conclusions: Rather than only focusing on individuals' behaviour, interventions could include changes to health service configuration and accessibility, and societal changes to increase coping ability.